Pemberdayaan Masyarakat Melalui Pembuatan Sabun Berbahan Dasar Minyak Jelantah Sebagai Upaya Mendukung Desa Wonoasri Kecamatan Tempurejo Kabupaten Jember Dalam Menuju Program Kampung Iklim (Proklim) - ratnasari, tri; Tri Handoyo; Didik Pudji Restanto; Parawita Dewanti (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Climate change is a change in the pattern, intensity or shift in the main climate parameters that will have an impact on ecosystems and humans. The impacts of climate change have been felt by humans. To reduce the impacts felt, the government established a climate village program (ProKlim) which combines mitigation and adaptation efforts. Wonoasri Village is one of the buffer villages that borders directly on Meru Betiri National Park. Wonoasri Village has made many efforts to mitigate environmental changes by developing alley forests and yard forests. Apart from that, adaptation efforts have also been carried out by forming joint business groups (KUBE) for community empowerment. Adaptation activities can be carried out by reducing the impact of change by reducing, reusing and recycling waste produced in an area. The joint business group in Wonoasri village includes a creative economy business group that operates in several business objects, one of which is the snack business group. This business group was founded in 2017 and is still actively producing until now. However, there is concern among the village community about this business group because the snack business group produces a lot of used cooking oil waste, almost 20 liters per week. So far, used cooking oil waste is simply thrown away in the yard. Not only from KUBE snacks, used cooking waste that is thrown away without processing also comes from the kitchen activities of village communities. The lack of adaptation efforts for used cooking oil waste produced by KUBE snacks and the Wonoasri village community will certainly pollute the environment. Therefore, the aim of this activity is to develop and encourage environmental adaptation through training in making soap made from used cooking oil as an effort for Wonoasri Village to become one of the ProKlim Villages in Jember Regency. This program is carried out through program outreach activities, workshops on making soap from used cooking oil as well as monitoring and evaluation. Socialization and training activities will be carried out simultaneously on Monday 10 July 2023 from 08.00 to 15.00. The result of the outreach and training is that the people of Wonoasri village know the impact of used cooking waste and can process used cooking waste into soap products. Monitoring will be carried out in August to see the sustainability of the program. KEYWORDS: used cooking soap, proklim, Wonoasri